2019
DOI: 10.1007/s10834-019-09656-w
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Gender Segregation in Turkey: The Vertical and Horizontal Dimensions

Abstract: This paper investigated occupational gender segregation and its vertical and horizontal dimensions in Turkey. In order to explore the extent of inequality entailed in occupational gender segregation (measured by the vertical dimension), average pay levels across occupations were used. In addition to the economic inequalities captured by pay, aiming to explore the social inequalities inherent in occupational segregation, Cambridge Social Interaction and Stratification Scale scores across occupations were used. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 48 publications
(67 reference statements)
3
8
0
1
Order By: Relevance
“…Based on the case, the main occupations of workers are more segregated in jobs with a high average wage or jobs with high social stratification such as professionals, other workers, and service business workers. This is in line with the study ofGedikli (2020) who proves that the level of segregation is high in occupations with high social stratification. The same condition was revealed by Salardi (2016) who found that overall gender was separated based on the composition of jobs with high social stratification.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Based on the case, the main occupations of workers are more segregated in jobs with a high average wage or jobs with high social stratification such as professionals, other workers, and service business workers. This is in line with the study ofGedikli (2020) who proves that the level of segregation is high in occupations with high social stratification. The same condition was revealed by Salardi (2016) who found that overall gender was separated based on the composition of jobs with high social stratification.…”
supporting
confidence: 91%
“…Apart from vertical segregation, differences also occur in horizontal segregation as revealed by Gedikli (2020) with the results of the study that the integration of women is very low in the labor market. This is also evidenced by Emerek et al (2003) who found that there was a positive difference between the level of women's employment and the segregation of occupations (for example, a relatively lower rate of gender segregation by occupations is characterized by lower employment rates for women).…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…It has been found that having a positive attitude toward science has a positive impact on students' science achievement score (Geesa, Izci, Chen, and Song, 2020) and if girls cannot identify themselves with this prototypical image, they would be less likely to aspire to become one (Gauthier, Hill, McQuillan, Spiegel & Diamond, 2017). The research also showed that women working in atypical female employment sectors are either overqualified or they are less rewarded than men (Gedikli, 2020).…”
Section: Underrepresentation Of Women In Technology Developmentmentioning
confidence: 94%
“…Usually, the coefficient of variation is used to represent the degree of segregation. For example, ethnic minorities in America only get low-wage jobs when they are allowed to work, and better jobs are left to the members of the white privileged class [ 10 12 ]. If all occupations are isolated, the index is 100%.…”
Section: Research Model On the Impact Of Utcp On Female Employmentmentioning
confidence: 99%